Theoretical and practical bases of work on the portrait in oil painting as the basis of mastering the professional and creative knowledge - V.V. Mishurovsky (Academy of Cognitive and Natural Sciences, 2009)
The article describes the ways of formation of theoretical and practical bases of work on the portrait.